Identification of Suitable Reference Genes for Normalization of Real-Time Quantitative Polymerase Chain Reaction in an Intestinal Graft-Versus-Host Disease Mouse Model - Li, X.; Qiao, J.; Yang, N.; Mi, H.; Chu, P.; Xia, Y.; Yao, H.; Liu, Y.; Qi, K.; Yan, Z.; Zeng, L.; Xu, K. (Transplantation proceedings, 2015)
With the development of real-time quantitative polymerase chain reaction (RT-qPCR) and intensive research on acute graft-versus-host disease (GVHD), selecting the best reference gene for normalization of RT-qPCR analysis in a GVHD model becomes more and more important. In this study, we aimed to identify suitable reference genes for mRNA studies in an intestinal GVHD mouse model after bone marrow transplantation (BMT). BALB/c recipients received 7.5 Gy total body irradiation (TBI) followed by injection of 5 × 106 bone marrow cells, without infusion of spleen cells for BMT, with infusion of 5 × 105 or 2.5 × 106 spleen cells for mild or moderate GVHD, respectively. Healthy mice were chosen as normal control subjects. Duodenum, jejunum, ileum, colon, and small intestine were collected at days 7, 14, 21, and 28 after transplantation. Transcription levels of 9 candidate genes, B2M, SDHA, HPRT, ACTB, GAPDH, HMBS, TBP, YWHAZ, and RPLP0, in each tissue were measured with the use of RT-qPCR. Combined data from these tissues in each group were defined as all samples. The expression stability of these genes was analyzed with the use of Genorm, Normfinder, Bestkeeper, and ΔCt. Our results showed that in all samples, ACTB and HMBS displayed the highest and lowest expression levels, respectively. Genorm identified HRPT and SDHA as the most stable reference genes, whereas Normfinder and ΔCt method showed HPRT as the most stably expressed gene. Bestkeeper ranked YWHAZ and HPRT as the top 2 most suitable genes. In conclusion, HPRT was recommended as the most suitable reference gene after comprehensive ranking, suggesting that it could be used as an internal control for mRNA studies in intestinal GVHD after BMT. •We examined gene expression in an intestinal GVHD mouse model.•ACTB and HMBS displayed highest and lowest expression levels, respectively.•Genorm identified HRPT and SDHA as the most stable reference genes.•Normfinder and ΔCt identified HPRT as the most stable reference gene.•Bestkeeper identified YWHAZ and HPRT as the most stable reference genes.•HPRT was recommended as the most suitable reference gene.